Flexibility point of customer relationship management system based on user perspective. - Subramaniam, Hema; Zulzalil, Hazura; A. Jabar, Marzanah; Hassan, Saadah (Foundation of Computer Science, 2013)
Software is an essential asset of an organization in organizing business process. Thus, demand for software gradually increase from day-to-day. However, due to the complex structure of a software and tedious software design has cause delays in making it to be available in market. Consequently it increases the needs for customizing software from existing system. Under those circumstances, software customization is influenced by the flexibility of software that indicates how easy the software is modified to suit the current environment. Thus, the easiness is determined by the flexibility point that resides in software. Since flexibility is a desirable software quality characteristic, determination of flexibility point is essential. In this case, user role transformation from one domain to another domain has been viewed as flexibility point that triggers changes into the software. To demonstrate flexibility point exist at the user role, this study emphasize on the change of class design from Customer Relationship Management System (CRMS) to Tuition Centre Management System (TCMS). As a result, some slight modification on the user oriented class attributes and methods effect the changes on other associated classes. Certainly, slight modification only can be made if the user-oriented class definition is written as general purpose rather than dedicated to one system. Therefore, proper definition of user-oriented class assists in promoting flexibility and at the same time it has been view as software flexibility point.